Validation of Posturographic Measurements in Adolescents. Issue 7 (August 2018) - Christensen, Ida Kolind; Deilami, Seyedeh Shadi Javadian; Amiri, Sahar; Nissen, Monika Holm; Devantier, Louise; Ovesen, Therese
Abstract : Objective: The objectives of the present study were to validate the test–retest reliability of static posturography in healthy adolescents aged 13 to 16 years, to identify the most reliable and least variable measurements. Patients: Thirty-two healthy pupils from Skåde Skole participated in this study. Intervention: Static posturography. Outcome Measures: Subjects were tested for 32 seconds in eight trials (eyes open/eyes closed, on stable ground/foam pads, head neutral/head turned) by using a Tetrax platform. Testing included two rounds of trials and postural regulation was assessed by measuring sway during the eight trials. Results: We found statistically significant lower sway scores during round two in position NO; a similar trend was seen for position NC, PO, HR, HL, and HB, but was not statistically significant. For position PC and HF an increase was seen, but not statistically significant. Conclusion: The most reliable and least variable measurements include position NO, NC, PO, and PC. Influence of all three systems involved in maintaining balance is tested in these positions. Static posturography can easily be implemented in a clinical setting as the equipment does not take up much space and is easy to use and instruct the test subjects about. Finally, the costs related to the static posturography are considerably lower compared with dynamic posturography equipment. However, static posturography might not be challenging enough when testing athletic individuals.